Influence of food type, oil type and frying frequency on the formation of trans-fatty acids during repetitive deep-frying. (May 2023) - Manzoor, Shaziya; Masoodi, F.A.; Rashid, Rubiya
Abstract: Frying oil quality is immensely affected by frying frequency, type of food and oil used for frying. The main aim of this study was to investigate the impact of food type (fish, chicken, potato and peas), oil type (soyabean and mustard oil) and frying frequency on the trans-fatty acid (TFA) formation in both deep-fried oils and the foods fried in these oils. Increase in frying-time leads to an increased TFA content with trans18:1 in higher concentration (0.87–2.41%) followed by trans18:3 (0.38–1.70%) and trans18:2 (0.22–1.37%) with trans18:2 formed at a higher rate comparatively. Highest TFA was accumulated in soyabean-oil used for frying fat rich food followed by protein, carbohydrate (CHO) and vegetable-based foods as compared to mustard oil-based foods. Total TFA in soyabean-oil used for frying fish after 25th hour was 5.48% and the TFA content retained in fried fish after 50 frying cycles was 3.98%. TFA content increased 2.56, 2.98, 3.29-folds and 2.38, 2.70 and 3.15-fold for one, two and three frying per half hour while frying fish-fillets in soyabean and mustard oil respectively. Oxidative stability and TFA formation were found to have a direct correlation and soyabean oil used for frying fat rich group shows higher degradation compared to mustard oil in terms of acid value, peroxide value, TBARS value and p-anisidine value. Thus, proximate composition of a food and fatty acid composition of an oil plays a key role in the formation of TFA during deep frying. Highlights: Effect of frying frequency, food type and oil type on TFA formation was investigated. Thermal oxidative stability follows this order: vegetable>potato>chicken>fish. Soyabean oil used for frying fish displays lowest thermal stability and highest TFA. Formation of TFA coincides with that of lipid oxidation. Rapid exchange of fats take place between the frying oil and frying food.